2016
DOI: 10.3233/jad-151172
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Frailty Predict Changes in Cognition in Older Men: The Honolulu-Asia Aging Study

Abstract: Objectives As cognitive decline mostly occurs in late life, where typically it co-exists with many other ailments, it is important to consider frailty in understanding cognitive change. Here, we examined the association of change in frailty status with cognitive trajectories in a well-studied cohort of older Japanese-American men. Methods Using the prospective Honolulu-Asia Aging Study (HAAS), 2817 men of Japanese descent were followed (aged 71–93 at baseline). Starting in 1991 with follow-up health assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 65 publications
3
38
0
Order By: Relevance
“…Some attribute this discrepancy to neural reserve, which is potentially maintained through cognitive activity [75]. Another possibility supported by the current research is that frailty may deplete neural reserve, thus cognitive impairment tends to increase as individuals become frailer [6]. The fact that brain pathology commonly associated with dementia and AD has also been found to be associated with frailty provides further support for the role of frailty in neural reserve [76].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Some attribute this discrepancy to neural reserve, which is potentially maintained through cognitive activity [75]. Another possibility supported by the current research is that frailty may deplete neural reserve, thus cognitive impairment tends to increase as individuals become frailer [6]. The fact that brain pathology commonly associated with dementia and AD has also been found to be associated with frailty provides further support for the role of frailty in neural reserve [76].…”
Section: Discussionsupporting
confidence: 52%
“…For example, baseline frailty measured in three ways (i.e., FI from a comprehensive geriatric assessment, clinical frailty score, and the frailty phenotype) was associated with changes in cognitive function over time regardless of which frailty measure was used [4]. Armstrong and colleagues found frailty was associated with declines in cognitive function over a 3-and 6-year period [22] and that within person changes in frailty were associated with changes in cognition even after taking into consideration baseline frailty [6]. Buchman and colleagues found frailty predicted rate of cognitive decline and incident AD and suggested that frailty occurs before dementia [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frailty criteria also seem to be associated with cognitive impairment. A longitudinal survey involving 2,817 Japanese men showed that individual frailty factors were associated with a 16 to 18% reduction in their global cognitive status 36 . In another study, slowness and physical exhaustion ( fatigue) were associated with a reduction in global cognition 37 .…”
Section: Discussionmentioning
confidence: 99%
“…One should be to test ‘lead-lag’ effects, that is, whether changes in cognition follow changes in frailty, or vice versa, or whether there is interplay between these. While it is worth noting that there was little evidence for shared declines in physical and cognitive functions in the Lothian cohorts,5 6 multilevel growth curve analysis using the Honolulu-Asia Aging Study suggests that within-person increases in frailty predicted cognitive decline 9. This does not rule out dynamic interplay however, since Gale et al also found that decline in cognitive function predicted Fried frailty in the Lothian Birth Cohort 1936 (ref.…”
mentioning
confidence: 99%